(untitled) (Bangladesh Journal of Neurosurgery, 2019)
Background: Peripheral nerve injury is a common condition. Though it is not life threatening, it may cause disability to a person. In this study we have analysed our experience of anastomosis of injured nerves. Materials and methods: This is an observational study that was done within a period from January 2014 to December 2018. 13 patients with injury to the nerves were operated upon. There were 11 male and 2 female patients. All patients were followed up in OPD upto one and half years. 5 patients were lost from follow up, of these, two were female. Results: After surgery, touch returned in 5 patients. Of motor function,there was no improvement in 1 patient, grade 1 in 1 patient, grade 2 in 4 patients and grade 3 in 3 patients. Those who came earlier had better outcome, so had those with small injury and distal to the limb. Conclusion: peripheral nerve injury has to be repaired as soon as possible. The sooner it can be done the better will be the outcome. Bang. J Neurosurgery 2019; 9(1): 33-38